2020
DOI: 10.1101/2020.09.28.317438
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ColwelliaandMarinobactermetapangenomes reveal species-specific responses to oil and dispersant exposure in deepsea microbial communities

Abstract: Over 7 million liters of Corexit EC9500A and EC9527A were applied to the Gulf of Mexico in response to the Deepwater Horizon oil spill. The impacts of dispersants remain under debate and negative, positive, and inconclusive impacts have been reported. Here, metatrancriptomics was applied in the context of metapangenomes to microcosms that simulated environmental conditions comparable to the hydrocarbon-rich 1,100 m deep plume. Within this microcosm study, negative effects of dispersants on microbial hydrocarbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…TT1 cells with their environment, as evidenced by upregulated efflux pumps, other transmembrane transporter systems, chemotactic motility, and changed biofilm formation behavior ( Figure 3 B). Similar trends were also observed in two recent metatranscriptomic studies on Corexit affecting seawater microbial communities [ 8 , 82 ] and in situ analysis from the DWH subsurface plume [ 83 ], although it remains unclear to what extent the plume metatranscriptomic data were influenced by Corexit and/or oil exposure.…”
Section: Discussionsupporting
confidence: 83%
“…TT1 cells with their environment, as evidenced by upregulated efflux pumps, other transmembrane transporter systems, chemotactic motility, and changed biofilm formation behavior ( Figure 3 B). Similar trends were also observed in two recent metatranscriptomic studies on Corexit affecting seawater microbial communities [ 8 , 82 ] and in situ analysis from the DWH subsurface plume [ 83 ], although it remains unclear to what extent the plume metatranscriptomic data were influenced by Corexit and/or oil exposure.…”
Section: Discussionsupporting
confidence: 83%
“…The presence or expression of β‐oxidation genes such as fadE , fadA , and fadB have been observed in waters exposed to dispersed oil, both in field (Rivers et al, 2013 ) and incubation studies (Ribicic et al, 2018 ), but it remains unclear whether those findings are associated with the oil, dispersant, or both. Recent incubation studies have also demonstrated an upregulation of β‐oxidation gene transcripts in treatments that contained Corexit compared to oil‐only treatments and unamended controls (Doyle et al, 2020 ; Peña‐Montenegro et al, 2020 ).Based on the significant enrichment of fadE , fadA , and fadB genes at the 5‐day time point, increased β‐oxidation of chemical compounds was likely occurring in the presence of Corexit and oil + Corexit relative to oil‐only or the control. This agrees with previously reported chemical loss data from this experiment, which showed that the majority of Corexit surfactant loss occurred within 5 days and the majority of oil loss within 10 days (Figure 3 ; Gofstein et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The successive pattern of hydrocarbon-degrading bacteria is likely a result of a combination of the dynamically shifting availability of oil components and of the nutrients available for oil-degrading bacteria . Both of the initially stimulated genera, Oleispira and Colwellia , are often associated with the early stages of oil spill situations. , The initial stimulation of Oleispira and Colwellia was probably due to their characteristic metabolic features, such as versatile metabolic enzyme systems and opportunistic growth strategies. , …”
Section: Discussionmentioning
confidence: 99%
“…22,60 The initial stimulation of Oleispira and Colwellia was probably due to their characteristic metabolic features, such as versatile metabolic enzyme systems and opportunistic growth strategies. 48,61 One of the later bloomers, Cycloclasticus, is a cosmopolitan genus that is detected commonly in oil biodegradation studies 22,49 and is responsible for mineralization of aromatic compounds. 62 Cycloclasticus species could struggle to compete with fast-growing alkane degraders for nutrients, and typically, they do not dominate the community until after the early bloomers decline.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%